The Intersection of Technology and Journalism: Exploring the Impact of New Media, Digital Media, and AI on Data and Robot Journalism on the Internet of Things Era - Alzubi, Ahmad (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
The field of journalism is undergoing a fast transformation as a result of technological advancements such as new media, digital media, and artificial intelligence (AI), all of which are redefining the method in which news is collected, evaluated, and disseminated. This shift has been further hastened by the emergence of the Internet of Things (IoT), which has led to the increased prevalence of data-driven and robot journalism. The purpose of this research paper is to investigate the effects that the recent advances in technology have had on journalism, with a particular emphasis on data journalism and robot journalism. We emphasize the advantages and problems of these new kinds of journalism and give insights into how journalists may effectively adapt to the changing technology environment by drawing on a thorough literature study. In addition, we highlight the benefits and challenges of these new forms of journalism.